Optimalisasi Pemanfaatan Aplikasi Canva dalam Pengembangan Bahan Ajar Digital di SDN 6 Mulang Maya - Rohmani; Mahendra, Yasinta; Apriza, Berta; Iqlima, Runa; Ardiasyah (Jurnal Abdimas Nusantara, 2025)
The rapid development of information technology requires teachers to transform from mere information providers into creative facilitators capable of designing digital learning experiences. However, teachers at SDN 6 Mulang Maya still face challenges in developing digital teaching materials due to limited technical skills and a lack of adequate training. This community service project aims to enhance teachers' competence in utilizing the Canva application as an instrument for developing interactive, engaging, and relevant digital teaching materials. The implementation method consisted of three main stages: planning (needs assessment), implementation (workshops and direct demonstrations), and evaluation and monitoring. The participants included 8 teachers from SDN 6 Mulang Maya. The results indicated a significant improvement in teachers' understanding and practical skills in operating Canva features, ranging from template utilization to interactive graphic element design. Based on the evaluation results, 80% of participants were able to independently design digital teaching materials ready for classroom implementation. In conclusion, this intensive mentoring program effectively increased teachers' confidence and digital competence, which is expected to foster a more innovative learning environment and boost students' learning motivation in the digital era.